Q. 15.0( 3 Votes )

Mark the correct

Answer :

Given that


A = {x ϵ R: –1 ≤ x ≤ 1} = B


C = {x ϵ R: X ≥ 0}


S = {(x, y) ϵ A × B: x2 + y2 = 1}


S0 = {(x, y) ϵ A × C: x2 + y2 = 1}


x2 + y2 = 1


y2 =1 - x2



y ϵ B


Hence, S defines a function from A to B.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in theMathematics - Exemplar

State True Mathematics - Exemplar

State True Mathematics - Exemplar

State True Mathematics - Exemplar

Let A = {1, 2, 3}Mathematics - Exemplar

Show that the relMathematics - Board Papers

Let N denote the Mathematics - Board Papers